110 Partnering with industry to develop future clinical leaders. (December 2018) - Poisson, J; Hothi, D; Sharma, S; Parish, E; Skellett, S
Abstract : Background: Morgan Stanley's relationship with Great Ormond Street Hospital (GOSH) began in 2007. As a corporate sponsor, they have donated much needed facilities for staff and patients. In addition, Morgan Stanley employees volunteer their time to work with young people and staff, providing support and mentoring. Methods: A Professional Development Programme PDP was designed to address the professional development needs of doctors, nurses, allied health professionals (AHPs) and admin staff at various bands in the hospital structure. The programme was structured on three levels, catering to varied experience. Level 1 for junior members of staff, Level 2 middle grade and Level 3 for the senior members of the organisation. Level 1 introduced professionalism in the National Health Service (NHS). More advanced levels focused on building NHS wisdom, covering areas such as leadership, self-awareness, quality improvement and finances. The Morgan Stanley team offered their expertise delivering sessions on topics including financial administration techniques, business case writing and team management. Results: On average, 16 delegates attended each course. All professional areas were represented, from various clinical specialities. The face-to-face sessions were a mixture of lectures, learning games, flipped classrooms, action learning sets and reflective practice. 100% provided feedback and all agreed, or strongly agree, the course was relevant, well facilitated and it would influence their future practice. Conclusion: Leadership and professional development are important in upskilling the workforce and staff retention. Having a multi-professional audience provided a great dynamic to the sessions; participants gained a respect for the work their colleagues do on the front line or the back office. There is much benefit in working with other industries. The private sector has a focus on resource efficiencies, something the public sector needs. Setting the sessions off-site gave participants an opportunity to remove themselves from the clinical setting, allowing them to immerse themselves into the educational offering.